Adjuvant psychotherapy in early-stage bipolar disorder: A protocol for systematic review and meta-analysis. Issue 14 (9th April 2021) - Chen, Qianfang; Zhou, Yuanyue; Lv, Huifen; Ma, Caie
Abstract: Objective: There is no systematic review or meta-analysis to evaluate the efficacy of adjuvant psychotherapy in early-stage bipolar disorder. Therefore, the goal of this meta-analysis is to examine the evidence supporting psychotherapy as an efficacious approach to treating bipolar disorder. Methods: Seven electronic databases including Web of Science, Embase, PubMed, Wanfang Data, Scopus, Science Direct, Cochrane Library were searched in March 2021 by two independent reviewers. Data extraction was performed independently, and any conflict was resolved before final analysis. Only randomized clinical trials were included in this study. The trial entails 1 primary outcome measure (relapse) and several secondary outcome measures: time to relapse, relapse rate, days missed at work/school (record, interview), and social functioning level. The risk of bias assessment of the included studies was performed by 2 authors independently using the tool recommended in the Cochrane Handbook for Systematic Reviews of Interventions. Results: We hypothesized that combined psychotherapy and pharmacological interventions would be superior to pharmacological interventions alone regarding the time to relapse into a manic or depressive episode. Conclusion: This study expects to provide credible and scientific clinical evidence for the efficacy and safety of combined psychotherapy and pharmacological interventions in the treatment of bipolar disorder. OSF registration number: 10.17605/OSF.IO/ZGS6W